The whiteness of white-collar crime in the United States: Examining the role of race in a culture of elite white-collar offending - Sohoni, Tracy (Theoretical criminology, 2021)
While the role of race has been heavily scrutinized in terms of minority involvement in crime, it has remained largely invisible for Whites despite indications that Whites are overrepresented as offenders in elite white-collar crimes. We propose a theoretical model detailing how “whiteness” encourages cultural adaptations conducive to elite white-collar crime in contemporary US society. Many middle- and upper-class US Whites live in environments of relative social isolation, both geographically (in terms of schools and neighborhoods) and culturally (as mainstream media largely reflect the lived realities of middle- and upper-class Whites). When this social isolation is combined with financial advantage, it serves to block the development of empathy toward outgroups and increases feelings of individual entitlement, which leads to the formation of crime-specific cultural frames that include neutralizations and justifications for elite white-collar crime. We argue that whiteness plays a role that is independent from (but exacerbated by) socioeconomic status, and is an important contributor to the generative worlds from which many white-collar criminals emanate.